Multiculturalism and Identity Negotiation among the Suku Laut in Coastal Community Development Dynamics in Bintan Regency, Indonesia - MARISA ELSERA; GLORY YOLANDA YAHYA; ELFA OPRASMANI; HADLI LIDYA RIKAYANA; DESRI GUNAWAN (Jurnal Moral Kemasyarakatan, 2026)
This study aims to analyze the practices of multiculturalism in the everyday lives of Orang Suku Laut (OSL), Bajo, and Bugis communities in Kawal, a coastal area inhabited by diverse ethnic groups with distinct cultural backgrounds, livelihoods, and social histories. The transition of OSL from a highly mobile maritime lifestyle to a more settled way of life has significantly influenced social relations and identity construction within this multiethnic community. This research utilized a qualitative approach, specifically employing a case study method. Data were collected through participant observation, in-depth interviews with members of the OSL, Bajo, and Bugis communities, and documentary analysis. The study was informed by theories of multiculturalism and identity negotiation, particularly Fredrik Barth’s concept of ethnic boundaries and Homi K. Bhabha’s notion of the third space. The findings reveal that multiculturalism in Kawal is primarily manifested through everyday social interactions, economic cooperation, and the mutual adaptation of cultural values among ethnic groups. Identity negotiation emerges as a crucial strategy through which OSL maintains its cultural existence while adapting to the dynamic realities of multiethnic life.